(36 3/4" + 36 3/8" + 371/2" +z) /4 = 36 5/8"
This is the equation that you would get for the average. Now we just solve for z.
Following PEMDAS you have to mulitply the equation by 4 to get rid of the divide by 4 part.
4( (36 3/4" + 36 3/8" + 371/2" +z) /4 = 36 5/8)
Which does this
36 3/4" + 36 3/8" + 371/2" +z = 146 1/2"
Now you have to add and subtract to get "z" by itself.
36 3/4" + 36 3/8" + 371/2" = 110 5/8"
(110 5/8" + z = 146 1/2" ) -110 5/8"
z= 35 7/8", so the answer is b
Answer:
1. a (s^7)
2. b (g^11)
Step-by-step explanation:
Answer:
3,312
lets be real who arctually looks at the step by step just use a calculator for this one
Answer:
I would just guess, but if i were to actually think about it, i would think C. I hope it helps, and blame it on me if you fail.
Step-by-step explanation: